The "privatization" of municipal debt - Ivan T. Ivanov; Tom Zimmermann (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2021)
Using confidential loan-level data, we investigate the importance of bank loans in the debt structure of U.S. state and local governments. We show that most bank debt is closely substitutable with municipal bonds and that smaller, lower-income and less credit-worthy borrowers are more reliant on bank borrowing. Moreover, we document a sizable difference in the maturity structure of bonds and loans that allows municipalities to save on interest costs but that could also lead to diluting bondholders' claims. Such dilution concerns are amplified by governments substantially increasing bank borrowing in response to credit quality deterioration. This suggests the upward trend in bank borrowing will likely persist if fiscal positions continue to decline.
Keywords: H6; F18; M41; 330; state and local governments' debt; debt heterogeneity; fiscal shocks